2017
DOI: 10.1021/jacs.7b04449
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Reactivity Studies of Diarylmethyl Radical Pairs in Crystalline Tetraarylacetones via Laser Flash Photolysis Using Nanocrystalline Suspensions

Abstract: The nanosecond electronic spectra and kinetics of the radical pairs from various crystalline tetraarylacetones were obtained using transmission laser flash photolysis methods by taking advantage of aqueous nanocrystalline suspensions in the presence of submicellar CTAB, which acts as a surface passivator. After showing that all tetraarylacetones react efficiently by a photodecarbonylation reaction in the crystalline state, we were able to detect the intermediate radical pairs within the ca. 8 ns laser pulse of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…With these characteristics, the nanocrystal/microcrystal suspensions can strongly diminish the scattering of bulk powders and large single crystals during spectroscopic measurements . Previous work reported that nanocrystalline molecules will have shorter lifetimes compared to those of the corresponding molecules in the solution phase, which is thought to be caused by strong intermolecular interactions like π–π stacking and others that will intensively restrict the vibrations and rotations of the molecules in the crystal . Hence, if the photoswitching molecules are fabricated into the nanocrystals and microcrystals, one may expect to improve the sensitivity and ultrafast response times of these photoswitching materials and overcome the different drawbacks that exist for the bulk crystal and powder systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With these characteristics, the nanocrystal/microcrystal suspensions can strongly diminish the scattering of bulk powders and large single crystals during spectroscopic measurements . Previous work reported that nanocrystalline molecules will have shorter lifetimes compared to those of the corresponding molecules in the solution phase, which is thought to be caused by strong intermolecular interactions like π–π stacking and others that will intensively restrict the vibrations and rotations of the molecules in the crystal . Hence, if the photoswitching molecules are fabricated into the nanocrystals and microcrystals, one may expect to improve the sensitivity and ultrafast response times of these photoswitching materials and overcome the different drawbacks that exist for the bulk crystal and powder systems.…”
mentioning
confidence: 99%
“…To account for this phenomenon, the single-crystal structures were employed to illuminate the different dynamics of the CC bond molecules studied here. In the nanocrystal/microcrystal suspensions, due to the restriction of the crystal lattice, the photoisomerization processes of these molecules under light irradiation are accelerated to eventually lead to shorter lifetimes in the nanocrystals and microcrystals …”
mentioning
confidence: 99%
“…1−10 For example, using crystalline tetraarylacetones (1, R = CHAr 2 ; Scheme 1), we have shown that pulsed laser excitation of nanocrystals suspended in water 11 makes it possible to detect triplet radical pairs 3 RP-2 formed by the loss of CO and to follow their subsequent decay to the corresponding photoproduct 2 (R = CHAr 2 ). 12 The reaction starts by electronic excitation (step 1) and is followed by intersystem crossing (step 2) to the triplet excited state ( 3 1*), which goes on to cleave an α-bond (step 3) to form a strongly correlated triplet acyl−alkyl radical pair ( 3 RP-1). When R = CHAr 2 , there is a rapid spin-conserving loss of CO to form the relatively long lived triplet alkyl−alkyl radical pair 3 RP-2 (step 4), which goes on to the product 2 (step 7) through the singlet radical pair 1 RP-2 via a ratelimiting intersystem crossing step (step 6) shown to occur with time constants between 40 and 90 μs depending on Ar.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, we decided to explore suspending the crystalline solids in water via a modified reprecipitation method as a means to scale up the photochemical reactions. We have shown that crystalline suspensions react in a more homogeneous manner, increasing the reaction velocity and conversion. Thus, aqueous suspensions of 4 were prepared by dissolving the ketone in a minimal amount of acetone, which was added dropwise to rapidly stirring water with submicellar surfactant concentrations. The reprecipitated solids were collected via filtration and confirmed to be crystalline and of the same polymorphic phase as the bulk powders (Figure S2).…”
mentioning
confidence: 99%